Fifty key writers on photography - Durden, Mark. (Abingdon, Oxon : Routledge, 2013)
"Fifty Key Writers on Photography is a clear and concise survey of some of the most significant writers on photography who have played a major part in defining and influencing our understanding of the medium. It provides a succinct overview of writing on photography from a diverse range of disciplines and perspectives and examines the shifting perception of the medium over the course of its 170 year history. Key writers discussed include:Roland BarthesCharles Baudelaire Christian MetzHenri Cartier-BressonGeoffrey BatchenFully cross-referenced and in an A-Z format, this is an accessible and engaging introductory guide"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Photography; Photography literature; Technology writers -- Biography; Photographers -- Biography; Electronic books